The First Chromosome-level Genome Assembly of Cheumatopsyche charites Malicky and Chantaramongkol, 1997 (Trichoptera: Hydropsychidae) Reveals How It Responds to Pollution. (8th September 2022) - Ge, Xinyu; Jin, Jianfeng; Peng, Lang; Zang, Haoming; Wang, Beixin; Sun, Changhai
Abstract: Trichoptera is a highly adapted group of freshwater insects. They are generally more sensitive to dissolved oxygen and water quality than most freshwater organisms, and this sensitivity allows them to be used as reliable biological indicators of water quality. At present, there exists no chromosome-level genome of a hydropsychid species. Cheumatopsyche charites Malicky & Chantaramongkol, 1997 can successfully survive and thrive in polluted streams where other caddisflies are infrequent, suggesting that they are tolerant to latent contamination. Here we report a high-quality chromosome-level genome assembly of C. charites generated combining PacBio long reads and Hi-C reads. We obtained a genome assembly of 223.23 Mb, containing 68 scaffolds with an N50 length of 13.97 Mb, and 155 contigs (99.67%) anchored into 16 pseudochromosomes. We identified 36.12 Mb (16.18%) of the genome as being composed of repetitive elements, identified 369 noncoding RNAs, and predicted 8, 772 protein-coding genes (96.80% BUSCO completeness). Gene family evolution analyses identified 7, 148 gene families, of which 41 experienced rapid evolution. The expanded gene families were shown to be involved in detoxification metabolism, digestive absorption, and resistance to viruses or bacteria. This high-quality genome provides a valuable genomic basis for the study of trichopteran evolution.